Small‐size effect on physicochemical properties of micronized fish bone during heating. Issue 5 (17th February 2020) - Jiang, Yang; Zhang, Mengling; Yin, Tao; Du, Hongying; Xiong, Shanbai; Cao, Liwei; Liu, Ru
Abstract: The aim of the study is to investigate physicochemical properties of nano‐scaled fish bone (NFB) and micro‐scaled fish bone (MFB) during heating and improve their valorization by promoting their calcium release. For MFB, heating promoted its calcium release (from 0.7% to 2.2%) and solubility (from 4.6% to 11%) mainly by reducing the particle size (from 20.51 to 17.85 μm). However, the FT‐IR and XRD of MFB spectra showed small change during heating. For NFB, heating hardly changed its particle size but further destroyed the crystal and chemical structure of NFB. The solubility was significantly increased from 9.8% to 14.0%. After heating at 90°C, the sharper diffraction peaks of hydroxyapatite were also observed. The calcium release was significantly promoted from 9.0% to 14%. The results showed heating could more effectively promote the calcium release of fish bones when the particle size was reduced to nanoscale. Practical applications: Grass carp is the most productive freshwater fish in China. Fish bones are the main by‐product from fish processing. Fish bones can be added to food as a natural calcium sources. The aims of our research are to improve the calcium release of fish bones and promote application of fish bones in food fields. After the particle size was reduced to the nanoscale using wet ball milling, heating at common cooking temperature could significantly promote the calcium to release from fish bones.